The Role of SOCS2 Cytokine Signaling Suppressor in the Regulation of ProInflammatory Activity of Whole Blood Cells after Lower Respiratory Tract Infection - S. S. Bondar; I. V. Terekhov; V. S. Nikiforov; V. K. Parfenyuk; N. V. Bondar (SINAPS LLC, 2022)
The aim of the investigation was to study the relationship between the content of whole blood in mononuclear leukocytes in pneumonia and in apparently healthy individuals of cytokine signaling suppressor 2 (SOCS2) with the production of cytokines (TNFα, TGFb, IFNα, IFNβ, IFNγ, IL-1β, IL-2, IL-4, IL-5, IL-10, IL-12, IL-17A, RAIL-1, RANTES) and individual factors of the NF-kB and JAK / STAT signaling pathways (NF-kB2, p65, p50, STAT1, STAT3, STAT5B, STAT6). Materials and research methods. The research material was mononuclear cells isolated from venous blood samples, as well as blood plasma of practically healthy individuals and patients with pneumonia. In nuclear-cytoplasmic lysates of mononuclear blood cells, the concentration of the components of the nuclear transcription factor NF-κB, p65, p50, NF-κB2, factors STAT1, STAT3, STAT5B, STAT6, and protein SOCS2, was assessed by enzyme immunoassay. We also determined the concentration of TNFα, IL-1β, TGFb, IFNα, IFNβ, IFNγ, IL-1β, IL-2, IL-4, IL-5, IL-10, IL-17A, RAIL-1, RANTES. The results of this study indicate that the stage of pneumonia convalescence is accompanied by dysregulation of the production of the main proinflammatory cytokines, manifested by a decrease in the level of TNFα, TGFb, RANTES, IL-4, IL-17A, IFNβ, IFNγ and an increase in the production of IL-2 and IFNα. Against this background, a decrease in the phosphorylation of the STAT3 and STAT4 factors was noted, as well as a decrease in the content of p50 and p65 proteins in MNCs. These changes were associated with an increased content of the SOCS2 factor in MNCs. The analysis showed that an increase in the content of SOCS2 in MNCs from the minimum level determined by the concentration corresponding to the 1st quartile of the sample (1.3 ng / ml) to the maximum, determined by the 4th quartile of the sample (1.7 ng / ml) is associated with a decrease in production IL-1β, IL-4, IL-4, IL-5, IL-10, IL-17A, TGFb, RANTES and IFNβ against the background of an increase in the level of INFα, INFγ and IL-2. Changes in cytokine production were accompanied by an increase in STAT5B, STAT4, and NF-kB2 levels and a decrease in STAT3 phosphorylation. a decrease in the content in the cell of the components of the nuclear transcription factor NF-κB, in particular, p50, p65. Conclusion. The peculiarities of the relationship of SOCS2 with the studied factors suggests that its high level helps to limit the production of proinflammatory cytokines, in particular those produced by type 2 T-helpers and Th17, stimulates an increase in ICC sensitivity to IL-2 and stimulation of type 1 T-helpers. These effects are realized due to an increase in the phosphorylation of the STAT5 and STAT4 factors, a decrease in the STAT3 activity, and a change in the ratio of the components p50, p65 and NF-κB2 of the nuclear transcription factor NF-κB in the cell.